A constituição do ethos discursivo e da identidade do ídolo esportivo Neymar - Coquieri, Fábio (2021)
This Dissertation has as its theme the study of the figure of Neymar in the media space and the way in which the media discourse shows its discursive ethos. In addition, we have the following objectives: to analyze how news is constructed in the media space, identifying the strategies that the enunciator uses to build the image of the athlete Neymar through the use of different languages, to issue the same news in Folha de S newspapers .Paul and Now. To support our research, we rely on the French Discourse Analysis, from the perspectives of Maingueneau and Charaudeau, to understand how news enunciators select and shape journalistic texts, and what are the meaning effects negotiated by these productions. The corpus consists of newspaper covers, seized as a speech and published between 2009 and 2018 by the newspapers Folha de S. Paulo and Jornal Agora. The choice of the theme for this research focuses on concerns aroused over the last decade regarding the media and its power of discursive articulation and the interest in verifying how the media creates Neymar's image